Ethylene Production from C3+ Olefins Through Combined Catalytic Cracking and Metathesis Reactors - Egamberdiyeva Zulxumor Abduraxmonovna (Genius Journals, 2022)
This article will consider the possible combination of catalytic cracking and metathesis processes and the calculation of economic efficiency to obtain ethylene from C3+ olefins by process calculation in Aspen HYSYS software.
Keywords: Petrochemical production; polyethylene; metathesis; separation system